2016
DOI: 10.1177/2010105816633246
|View full text |Cite
|
Sign up to set email alerts
|

Y-shaped axillary arch muscle: A case report

Abstract: The axillary arch is a rudimentary part of the latissimus dorsi. Generally it has a single insertion either into tendon of the pectoralis major, coracobrachialis or fascia over the biceps. Clinically, this anomalous muscular slip is known to cause neurovascular compression of nearby structures. The present case reports an unusual bifurcated fibrous insertion of an axillary arch with Y-shaped limbs. The stem of this muscle was a fleshy belly measuring 7.8 cm. The upper limb of this muscle, measuring 5.6 cm, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The most common morphological description of the axillary arch is that they are bidirectional band with a solitary origin and insertion. Nevertheless, multiple studies have reported variations in their morphology, with Loukas et al, reporting the presence of numerous bands at the insertion sites 5 , while Shanthakumar et al reports the presence of an extraordinary 'Y' formed axillary arch with a bifid distal attachment, one to the short head of the biceps brachii, and the other to coracoid process 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common morphological description of the axillary arch is that they are bidirectional band with a solitary origin and insertion. Nevertheless, multiple studies have reported variations in their morphology, with Loukas et al, reporting the presence of numerous bands at the insertion sites 5 , while Shanthakumar et al reports the presence of an extraordinary 'Y' formed axillary arch with a bifid distal attachment, one to the short head of the biceps brachii, and the other to coracoid process 6 .…”
Section: Discussionmentioning
confidence: 99%